Society 5.0: A New Challenge to Legal Norms - Nabeel Mahdi Althabhawi; Zinatul Ashiqin Zainol; Parviz Bagheri (Sriwijaya Law Review, 2022)
Society 5.0 is a new term used to indicate the future world. This society is based on ubiquity, learning machines, the internet of things, big data, cloud computing, cryptography, and biometrics. All these technologies will be merged to create a new mode of life. The new way of life will inevitably influence human beingsâ€™ values, concepts, and conduct. The result of these changes will consequently bring challenges to many legal areas. This paper addresses the challenges that brought society 5.0 to legal norms. It utilises the analytical approach to examine the capability of pre-existing legal norms to cope with new realities created by society 5.0. The paper analyses the legal implications of society 5.0 in their sociological context. It presents a jurisprudential vision to establish legal norms compatible with the new society. Three fundamental principles should be considered to establish new legal. First, social facts that trigger legal regulation can simultaneously occur in multiple places. Secondly, what the study called duality of legal rules will not survive in society 5.0 era. Third, the paper turns the spotlight on new intelligent systems which may introduce new law addressees.